Risky Behaviors of Motorcycle Passengers: Field studies in Jakarta and Bekasi Areas - Triyanti, Vivi (Universitas Al Azhar Indonesia, 2024)
The behaviors of motorcycle drivers are rarely studied, while their behaviors caused considerable danger on driving safety. This study aims to identify risky behaviors of motorcycle drivers. This study was conducted in some roads in Jakarta and Bekasi by adopting the work sampling technique. The results showed that risky behaviors were mainly dominated by not wearing a helmet and by carrying more than one person. These behaviors were most commonly found in areas where it was perceived that there was no police and Electronic Traffic Law Enforcement (ETLE), especially in the Bekasi area. The presence of the police is crucial in preventing risky behavior of the drivers. Therefore, it is recommended to further ensure the presence of the police in areas prone to risky behaviors, especially when ETLE is not yet installed, or when it has not been fully applied. Keywords – Motorcycle, Passengers, Risky Behaviors, Work Sampling.